2015
DOI: 10.1371/journal.pone.0142937
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease as a Predictor of Atrial Fibrillation in Middle-Aged Population (OPERA Study)

Abstract: Non-alcoholic fatty liver disease (NAFLD) and atrial fibrillation (AF) are widespread diseases and have multiple common risk factors and comorbidities. No studies of association between ultrasonography-diagnosed NAFLD and AF exist in other than diabetic population. The goal of this prospective study was to study the value of NAFLD as a predictor of atrial fibrillation. This study had 958 subjects from the OPERA (Oulu Project Elucidating Risk of Atherosclerosis) cohort, and the mean follow-up time was 16.3 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 58 publications
1
98
0
11
Order By: Relevance
“…After excluding duplicates, based on the titles and abstracts of 89 citations (in accordance with the aforementioned exclusion criteria of the meta‐analysis), we initially identified 11 potentially relevant studies from PubMed, Web of Science and Scopus databases prior to December 14, 2018 (date last searched). After examining the full text of these 11 publications, we further excluded 2 studies, because of unsatisfactory inclusion criteria ( n = 1) or unsatisfactory outcome measures ( n = 1), as specified in the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding duplicates, based on the titles and abstracts of 89 citations (in accordance with the aforementioned exclusion criteria of the meta‐analysis), we initially identified 11 potentially relevant studies from PubMed, Web of Science and Scopus databases prior to December 14, 2018 (date last searched). After examining the full text of these 11 publications, we further excluded 2 studies, because of unsatisfactory inclusion criteria ( n = 1) or unsatisfactory outcome measures ( n = 1), as specified in the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common sustained arrhythmia in clinical practice and is a major health problem worldwide, owing to its associated morbidity and increased mortality . As it will be discussed in greater detail below, a number of observational studies have recently examined the association between NAFLD and risk of both prevalent and incident AF in middle‐aged and elderly individuals, but these have produced conflicting results …”
Section: Introductionmentioning
confidence: 99%
“…NAFLD has been shown to be associated with an increased risk of AF, independently of gender, age, hypertension, LV hypertrophy and PR interval[12,67,68]. Additionally, a prospective study of nearly 1000 subjects has reported that NAFLD is an independent risk factor of AF[69]. …”
Section: Clinical and Subclinical Cvd And Nafld Markersmentioning
confidence: 99%
“…The association between non-alcoholic fatty liver disease (NAFLD) and AF has recently been presented [7, 8]. The mechanisms that link these two entities are not completely understood, but it is reasonable to assume that this association is causal [7] and two-way.…”
Section: Introductionmentioning
confidence: 99%